1996
DOI: 10.1111/j.1540-8159.1996.tb03267.x
|View full text |Cite
|
Sign up to set email alerts
|

Initial and Long‐Term Evaluation of Escape Rhythm After Radiofrequency Ablation of the AV Junction in 50 Patients

Abstract: Between 1986 and 1994, 50 patients (mean age 63 +/- 13 years), 25 of whom had organic heart disease and presenting with atrial arrhythmias refractory to 5.6 +/- 1.6 antiarrhythmic drugs, underwent radiofrequency ablation (5 +/- 3 pulses by procedure; duration of pulses 50.5 +/- 32 s) of the proximal AV junction to create complete and permanent AV block. The escape rhythm was studied immediately after the procedure and during long-term follow-up. Immediately after the procedure, an escape rhythm was observed in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
9
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 20 publications
2
9
0
Order By: Relevance
“…As compared to the classical ablation at the AV‐node level, the ablation of the branches and fascicles of the His bundle are technically more challenging, and one would theoretically expect to see an escape rhythm at too low a rate or even no escape rhythm at all, which would then obligatorily require permanent pacing. Usually and after AV node ablation, an escape rhythm appears in 70–100% of the cases 6,7 . In the present case, a ventricular escape rhythm was observed between 35 and 45 bpm after complete AV block was induced.…”
Section: Discussionsupporting
confidence: 49%
“…As compared to the classical ablation at the AV‐node level, the ablation of the branches and fascicles of the His bundle are technically more challenging, and one would theoretically expect to see an escape rhythm at too low a rate or even no escape rhythm at all, which would then obligatorily require permanent pacing. Usually and after AV node ablation, an escape rhythm appears in 70–100% of the cases 6,7 . In the present case, a ventricular escape rhythm was observed between 35 and 45 bpm after complete AV block was induced.…”
Section: Discussionsupporting
confidence: 49%
“…These data are in contrast to the findings of Alison et al, in which 100% and 98% of the 45 patients had escape rhythms present immediately postablation and at 11 ± 8.3 month follow‐up, respectively 9 . Piot et al reported on 50 patients who underwent RF ablation 10 . Eighty percent of these patients had an escape rhythm immediately following the procedure and at a mean follow‐up of 36 months postprocedure, an escape rhythm was present in 83%.…”
Section: Discussionmentioning
confidence: 61%
“…However, concern remains regarding subsequent dependency on an entirely paced rhythm 3–6 and the possible sequela of unheralded pacemaker failure. The potential for this untoward outcome has led investigators to evaluate the presence and stability of escape rhythms following AV node ablation 7–13 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study evaluating escape rhythm adequacy after AV junction ablation (essentially those similar to this case) showed that 80% of patients had an adequate escape rhythm, and only 3 out of 40 patients lost their escape rhythm over 3-year follow-up. 9 Although an implantable monitor could be considered as an alternative management approach in this patient, ultimately the likelihood of sudden heart block must be balanced against the risks of prophylactic pacemaker implantation. Given the relatively low risk of complications associated with pacemaker implantation as compared with the small but potentially serious possibility of sudden catastrophic heart block, the decision to proceed with pacemaker implantation is reasonable in this case.…”
mentioning
confidence: 99%